2002
DOI: 10.1016/s0736-0266(01)00150-4
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor (VEGF)‐induced angiogenesis in herniated disc resorption

Abstract: Intervertebral disc herniation is a major cause of low back pain and sciatica. Spontaneous resorption of herniated disc (HD) is frequently detected by magnetic resonance imaging (MRI). Marked infiltration by macrophages and neo-vascuIarizatiol1~tioii are observed upon histogical exainiiiatioii of HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
115
0
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 27 publications
3
115
0
9
Order By: Relevance
“…It is difficult to reconcile this information with direct measurements of VEGF levels in the nucleus pulposus. A review of the pertinent literature indicates that there is no information on VEGF levels in the normal avascular disc; although not directly related to this investigation, it is known that VEGF, VEGF receptor 1 (VEGFR-1), and VEGFR-2 are expressed in herniated discs and discs that are forming granulation tissue (33).…”
Section: Discussionmentioning
confidence: 95%
“…It is difficult to reconcile this information with direct measurements of VEGF levels in the nucleus pulposus. A review of the pertinent literature indicates that there is no information on VEGF levels in the normal avascular disc; although not directly related to this investigation, it is known that VEGF, VEGF receptor 1 (VEGFR-1), and VEGFR-2 are expressed in herniated discs and discs that are forming granulation tissue (33).…”
Section: Discussionmentioning
confidence: 95%
“…5 Importantly, monocyte chemoattractant protein (MCP-1), a prototype of CC chemokine that contributes to the activation and recruitment of macrophages, 6 has been shown to be produced by IVD cells of the nucleus pulposus and annulus fibrosus 7 In addition, administration of MCP-1 in a rat autologous transplantation model of IVD results in a reduction in the size of the implanted disc. 8 Thus MCP-1 derived from IVD cells may play a critical role in natural HD resorption by triggering macrophage infiltration into HD tissue.…”
mentioning
confidence: 99%
“…TNF-a induced VEGF through the NF-kB pathway, which resulted in neovascularization of disc tissues. 5,15 The level of angiogenic activity in disc tissues was closely related to aging. 15 MCP-1 and MMPs play crucial roles in HD resorption.…”
mentioning
confidence: 99%
“…4,5 TNF-a stimulates matrix metalloproteinase (MMP)-3 in the disc in an autocrine/paracrine manner, causing further infiltration of Mj and degeneration of extracellular matrix. [4][5][6] However, the resorption mechanism has not been clarified.We previously revealed that nonthermal low-intensity pulsed ultrasound (LIPUS) stimulation was effective for enhancing resorption, and accelerating the rate of disc degeneration. 7 LIPUS therapy promotes bone fracture healing in human subjects, 8 modulates gene expression in osteoblasts or chondrocytes, 9,10 and influences second messenger activities related to angiogenesis.…”
mentioning
confidence: 99%
“…4,5 TNF-a stimulates matrix metalloproteinase (MMP)-3 in the disc in an autocrine/paracrine manner, causing further infiltration of Mj and degeneration of extracellular matrix. [4][5][6] However, the resorption mechanism has not been clarified.…”
mentioning
confidence: 99%